(untitled) (International Journal of Biomedical Research, 2016)
Background: Abnormal utrerine bleeding is the direct cause of significant health burden for women. Examination of endometrial biopsy is a challenge to pathologists , due to wide range of morphologic patterns. Aims and objectives: The present study was undertaken in cases of abnormal uterine bleeding and to correlate it with the clinical condition. Method: Atotal of 212 cases were included either by endometrial curettage or hysterectomy. Results: Major age group was 40-49 years. Menorrhagia was the commonest bleeding pattern. DUB was the largest group as regards the clinical diagnosis. Overall proliferative endometrium was the commonest histopathologiacal picture also it was the commonest picture of patients presenting with different bleeding patterns except of postmenopausal bleeding where atrophic endometrium was the commonest histological picture. Consistancy rate between curettage and hysterectomy was 56.25%. Conclusion: Abnormal uterine bleeding is a common debilitataing in women. Correct and timely diagnosis is necessary and specially to rule out cases of hyperplasia and carcinomatous focus for proper and timely management of patients.